2022
DOI: 10.1038/s41375-021-01485-x
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy and safety in a 4-year follow-up of the ELEVATE-TN study comparing acalabrutinib with or without obinutuzumab versus obinutuzumab plus chlorambucil in treatment-naïve chronic lymphocytic leukemia

Abstract: TO THE EDITOR Bruton tyrosine kinase (BTK) inhibitors have improved chronic lymphocytic leukemia (CLL) outcomes and offer a chemotherapyfree option [1]. The BTK inhibitor ibrutinib, alone or with a CD20 antibody, demonstrated better efficacy versus chemoimmunotherapy in treatment-naïve (TN) CLL [2][3][4]. However, cardiovascular toxicity is a concern with continuous ibrutinib use [5,6].Acalabrutinib is a next-generation, selective BTK inhibitor approved for CLL/small lymphocytic leukemia (SLL). Acalabrutinib, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
158
1
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 129 publications
(166 citation statements)
references
References 12 publications
2
158
1
5
Order By: Relevance
“…After 4 years of follow‐up within the ELEVATE TN trial, median PFS was not reached for the acalabrutinib‐containing arms versus 22.2 months for obinutuzumab‐chlorambucil in patients with unmutated IGHV. The 48‐month PFS rates were 86% for acalabrutinib‐obinutuzumab, 77% for acalabrutinib alone and only 4% for chlorambucil‐obinutuzumab 40 …”
Section: Firstline Treatment In Patients Without Del17p/muttp53mentioning
confidence: 98%
See 2 more Smart Citations
“…After 4 years of follow‐up within the ELEVATE TN trial, median PFS was not reached for the acalabrutinib‐containing arms versus 22.2 months for obinutuzumab‐chlorambucil in patients with unmutated IGHV. The 48‐month PFS rates were 86% for acalabrutinib‐obinutuzumab, 77% for acalabrutinib alone and only 4% for chlorambucil‐obinutuzumab 40 …”
Section: Firstline Treatment In Patients Without Del17p/muttp53mentioning
confidence: 98%
“…Although the trial was not powered for this comparison, the addition of obinutuzumab seems to improve responses and should be considered when initiating treatment with acalabrutinib. 40 The ELEVATE RR trial has compared ibrutinib to acalabrutinib in relapsed/refractory CLL patients and has demonstrated a similar efficacy of both treatments with a median PFS of 38.4 months in both arms while the median OS was not reached. With regard to side effects, acalabrutinib should particularly be considered for patients with cardiac conditions, as all-grade atrial or flutter incidence was significantly lower for acalabrutinib (9.4% vs. 16.0% for ibrutinib).…”
Section: Fit Patients With Mutated Ighv Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…Grade 3/4 AEs were reported in 71% of patients. The phase 3 ELEVATE TN (NCT02475681) study evaluated acalabrutinib treatment in previously untreated CLL patients (Table 3) [49,50]. A total of 535 patients were randomized to acalabrutinib alone, acalabrutinib + obinutuzumab, or chlorambucil + obinutuzumab arms.…”
Section: Acalabrutinibmentioning
confidence: 99%
“…In the CLL14 study, the venetoclax–obinutuzumab cohort reported similar changes in QoL compared to the chlorambucil–obinutuzumab group, 7 and formal QoL analyses of the ALLIANCE and iLLUMINATE cohorts are not available. More recently, the more selective BTKis acalabrutinib and zanubrutinib have demonstrated improved PFS compared to chemoimmunotherapy in the front‐line setting, 8,9 and reduced frequency of cardiovascular toxicities compared to ibrutinib in the relapse setting, 10,11 without demonstrating OS benefit. Overall, these trials reflect that OS benefits are difficult to demonstrate due to excellent outcomes achieved for most patients with currently available front‐line regimens and the wealth of salvage options 12–15 .…”
mentioning
confidence: 99%